2021
DOI: 10.3390/polym13132103
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Mechanical, Physical, Chemical and Thermal Properties of Microbial Composite Films by Integrating Sodium Alginate with Bacillus subtilis sp.

Abstract: Materials are the foundation in human development for improving human standards of life. This research aimed to develop microbial composite films by integrating sodium alginate with Bacillus subtilis. Sodium alginate film was fabricated as control. The microbial composite films were fabricated by integrating 0.1, 0.2, 0.3, 0.4, 0.5 and 0.6 g of Bacillus subtilis into the sodium alginate. Evaluations were performed on the mechanical, physical, chemical and thermal properties of the films. It was found that film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The weight loss curves continued until the third stage at 400–500 °C onwards, which, according to Wai Chun et al (2021) [ 45 ] is attributed to loss of soot by combustion or pyrolysis in this temperature range.…”
Section: Resultsmentioning
confidence: 92%
“…The weight loss curves continued until the third stage at 400–500 °C onwards, which, according to Wai Chun et al (2021) [ 45 ] is attributed to loss of soot by combustion or pyrolysis in this temperature range.…”
Section: Resultsmentioning
confidence: 92%
“…The second endothermic events (118.08 °C/−8.41 J/g (sample) and 117.70 °C/−150.11 J/g (control)) may perhaps be due to a depolymerization process with a formation of carbonaceous residue [ 42 , 43 ]. The exothermic events (252.37 °C/49.43 J/g (sample) and 255.37 °C/80.91 J/g (control)) probably corresponded to cleavage enthalpies such as the breakage of bonds within the complex [ 44 ]. The sample also showed two small endothermic events, which might be due to the influence of components in the buffer solution (where the phages are diluted) that increase the conformational stability through the electrostatic interactions of the present components [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, riboflavin is proposed to interact directly with outer membrane c-type cytochromes as a bridge between the working electrode and the cell for EET [ 121 ]. The redox mediators can be reduced or oxidized by the exoelectrogens and then be recycled electrochemically at the working electrode [ 122 ]. Indeed, García-Mayagoitia et al [ 108 ] concluded that the flavins excreted by the Bacillus subtilis strain and work as redox mediators were shown to enhance the bioelectricity production in the MFC system up to 105 mW/m 2 .…”
Section: Microbial Fuel Cell (Mfc)mentioning
confidence: 99%